2021
DOI: 10.1007/s00436-021-07107-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical forms of peritoneal larval cestodiasis by Mesocestoides spp. in dogs: diagnosis, treatment and long term follow-up

Abstract: Canine peritoneal larval cestodiasis (CPLC) is a little-known parasitological infestation of the peritoneal cavity of wild and domestic carnivores with Mesocestoides spp. larvae. While adult Mesocestoides tapeworms reside within the small intestine, the larvae occasionally penetrate the host’s intestinal wall, causing a potentially life-threatening peritonitis. Severity of infection as well as the host response influences the prognosis significantly, and early diagnosis and treatment are essential. However, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…infections in dogs can become severe, e.g. with the development of peritoneal larval cestodiasis, where larvae penetrate the host’s intestinal wall and cause potentially life-threatening peritonitis [ 78 ]. Although no human cases of infection with Mesocestoides spp.…”
Section: Discussionmentioning
confidence: 99%
“…infections in dogs can become severe, e.g. with the development of peritoneal larval cestodiasis, where larvae penetrate the host’s intestinal wall and cause potentially life-threatening peritonitis [ 78 ]. Although no human cases of infection with Mesocestoides spp.…”
Section: Discussionmentioning
confidence: 99%
“…Less often, nodular peritonitis has been caused by Mycobacterium microti, Actinomyces spp., or Nocardia spp. [ 35 , 36 ] or associated with larval stages of parasites such as Mesocestoides or Spirometra [ 37 ]. Microscopic and immunohistochemical studies in our case finally revealed granulomatous peritonitis associated with Leishmania and ruled out bacterial, fungal, and some parasitic etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, nodular lesions in the peritoneal cavity can be of infectious or non-infectious etiology. Interestingly, carcinomatosis has been confused with Mesocestoides -associated lesions [ 37 ]. Regardless of the origin of the peritoneal nodular lesion, microscopic examination is always recommended [ 38 ].…”
Section: Discussionmentioning
confidence: 99%